Effects of mat-feeding duration and different waterer types on nursery pig performance in a wean-to-finish barn - Potter, M. L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 3,680 weanling pigs were used in 2 experiments to determine the effects of mat-feeding strategies and different waterer types on pig performance and removal rates. In Exp. 1, a total of 24 pens (58 pigs per pen) were blocked by source farm and allotted to 1 of 4 gender (barrow or gilt) × feeding (control or mat-fed) treatments in a 27-d trial. Pigs were initially 15.4 lb. Control pigs did not receive any pelleted feed placed on mats, while pigs assigned to the mat-fed treatment were given 1.1 lb of pelleted diet on the mats 3 times daily for 6 d (with the exception of 1 pen, which was mat-fed for 5 d due to early mat disintegration). Pigs were weighed and feed intake by pen was recorded on d 0, 11, and 27 to calculate ADG, ADFI, and F/G. The numbers of removed and dead pigs were recorded, although individual pigs were not weighed. Thus, for Exp. 1, removed pig gain was not accounted for in ADG calculations. In Exp. 2, a total of 44 pens (52 pigs per pen) were allotted to 1 of 8 waterer types (swinging or pan) × gender (barrow or gilt) × mat-feeding duration (1.6 lb of pelleted feed given 3 times daily for either 3 or 7 d) treatments in a 32-d trial. Pigs were initially 13.6 lb. Waterer types evaluated in this study were a dual swinging waterer (Swinging; Trojan Plastic Waterswing, Trojan Specialty Products, Dodge City, KS) or an under-the-fence-line 14-inch pan waterer (Pan; Koca, Des Moines, IA). Pigs were weighed and feed intake by pen was recorded on d 0, 7, 20, and 32 to calculate ADG, ADFI, and F/G. Removed and dead pigs were tracked, and for Exp. 2, all removed pigs were individually weighed and included in calculations involving gain. Results from Exp. 1 indicate a difference (P = 0.04) in overall (d 0 to 27) removal percentage between control and mat-fed pigs. Fewer pigs fed on mats died or were removed from pens (5.9%) than control pigs (9.8%), with most removals between treatments occurring within the first 11 d (control: 8.0% vs. mat-fed: 4.6%; P = 0.03). Because of the difference in removal percentages, overall ADG and F/G tended to be improved (P = 0.06) for mat-fed pigs compared to the controls. However, average pig weights on d 0, 11, and 27 were not different (P ≥ 0.57) between treatments, indicating that the ADG advantage was due to the difference in removals rather than increasing weight gain of pigs remaining in the pens. Thus, the results of Exp. 1 indicate a benefit by feeding on mats for 6 d in reducing the percentage of removed pigs, but no advantages on growth performance were observed. For Exp. 2, removal percentages from d 0 to 7 were similar (P ≥ 0.17) regardless of treatment. By d 20 and through the end of the trial (d 32), a 2-way interaction (P = 0.03) was observed between water source and mat-feeding duration on removal percentages. Pigs that were fed on mats for 3 d and provided swinging waterers had the lowest removal rate among treatments. Biologically, it is difficult to understand why feeding on mats for 7 d would increase removals compared with 3-d mat-feeding for pigs provided with swinging waterers. Overall, there was a trend (P ≥ 0.08) for pigs using the swinging waterer to have increased ADG and improved F/G, resulting in pigs having a 1.4-lb numeric advantage in weight at d 32 compared with pigs drinking from the pan waterer. Much of the overall effect was due to pigs using the swinging waterer having improved (P = 0.02) ADG and F/G compared with pigs with pan waterer access in the early stages (d 7 to 20) of the nursery period. Overall, pigs fed on mats for 3 d had similar (P ≥ 0.12) ADG and F/G compared with pigs fed on mats for 7 d. There was a trend (P = 0.08) for pigs fed on mats for 7 d to consume more feed than pigs fed on mats for 3 d, although this increased intake did not result in significant changes in growth rate. Thus, F/G was poorer (P = 0.01) from d 0 to 7 for pigs fed on mats for 7 d vs. those fed on mats for 3 d. Results of these 2 experiments indicate that, in periods during these trials, performance and removal rates of pigs postweaning were able to be improved by feeding on mats and using swinging waterers instead of pan waterers.
Keywords: Swine; Growth; Mat-feeding; Waterer